Analysis of Denotative and Connotative Meanings in the Lyrics of the Song “Pikiran yang Matang” by the Band Perunggu - Dzaki Abqori Fadilla; Arju Susanto; Sukirno Sukirno (Journal of Social Research, 2026)
Song lyrics are a form of popular literary work that function not only as entertainment but also as a medium for conveying experiences, emotions, and the songwriter’s perspective on life. This study aims to analyze the denotative and connotative meanings of each line in the song “Pikiran yang Matang” by the band Perunggu, so that the message conveyed in the song can be understood more comprehensively. This research employs a descriptive qualitative method with a semantic approach. The research data consist of the text of the song lyrics “Pikiran yang Matang,” which are analyzed line by line. Data collection was conducted through a literature review, while data analysis was carried out by identifying denotative meanings as literal meanings and connotative meanings as additional meanings related to emotional experiences, symbols, and the social context underlying the song lyrics. The results indicate that, denotatively, the lyrics depict everyday conditions such as feelings of fatigue, mental disturbances, and simple daily activities. Connotatively, the song reflects mental exhaustion, boredom with energy-draining interactions, and the process of personal maturation in determining life priorities. Expressions such as “a mature mind” and “calm sea” function as symbols of a stable, peaceful emotional state after enduring various pressures. The song “Mind That Matang” conveys messages about intellectual maturity, emotional regulation, and efforts to live more calmly without being trapped in unnecessary drama, making it relevant to young people experiencing personal maturation.